2023
DOI: 10.35784/bud-arch.5499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crumb rubber and styrene-butadiene rubber additives on the properties of asphalt binder and the Marshall performance properties of asphalt mixtures

Diyar Khan,
Basit Ali,
Peilong Li
et al.

Abstract: The primary aim of this study is to evaluate the impact of incorporating crumb rubber (CR) and styrene-butadiene rubber (SBR) additives, ranging from 0% to 5% by weight of bitumen, on the performance of a bituminous concrete mixture using the wet process. Laboratory experiments, including the Marshall test, were conducted to establish the optimum bitumen content (OBC) for the hot mix. The study focuses on determining the optimal proportions of CR and SBR to achieve maximum strength. The results show that incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…An additive significantly affected the characteristics of the asphalt binder. Laboratory tests, including the Marshall test, were conducted to identify the optimum bitumen content (OBC) for the hot mix [24]. The Marshall mix-design technique was used to create hot mix asphalt mixes, with increasing proportions of recycled aggregates replacing coarse virgin aggregates (0%, 25%, 50%, and 75%).…”
Section: Experimental Program 21 Materials Selectionmentioning
confidence: 99%
“…An additive significantly affected the characteristics of the asphalt binder. Laboratory tests, including the Marshall test, were conducted to identify the optimum bitumen content (OBC) for the hot mix [24]. The Marshall mix-design technique was used to create hot mix asphalt mixes, with increasing proportions of recycled aggregates replacing coarse virgin aggregates (0%, 25%, 50%, and 75%).…”
Section: Experimental Program 21 Materials Selectionmentioning
confidence: 99%
“…The addition of Styrene Butadiene Rubber (SBR) latex to RAP mixes has been shown to enhance their viscoelastic properties, improve resistance to moisture damage, reduce rutting, and mitigate low-temperature cracking [31]. Results have shown that increasing CR and SBR improves strength, with an optimal mix containing 5% CR and 4% SBR [32]. The properties of the bituminous concrete mixture can be increased even more by including waste plastic [33].…”
Section: Introductionmentioning
confidence: 99%
“…Bio-oil modified binder was derived from diverse sources such as maize stalks, oak wood, shredded grass, and crumb rubber. These variants were utilized to modify both virgin binder and styrene–butadiene–styrene (SBS) incorporated binder 17 , 18 . Bio-oil modified binder from cedar sawdust, representing 9%, 6%, and 3% of the total binder mass, was incorporated into the specimens.…”
Section: Introductionmentioning
confidence: 99%